2018
DOI: 10.3390/nu10091314
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of Fatty Liver and Insulin Resistance in I148M PNPLA3 Carriers: Differences in Diacylglycerol (DAG) FA18:1 Lipid Species as a Possible Explanation

Abstract: Fatty liver is tightly associated with insulin resistance and the development of type 2 diabetes. I148M variant in patatin-like phospholipase domain-containing protein 3 (PNPLA3) gene is associated with high liver fat but normal insulin sensitivity. The underlying mechanism of the disassociation between high liver fat but normal insulin sensitivity remains obscure. We investigated the effect of I148M variant on hepatic lipidome of subjects with or without fatty liver, using the Lipidyzer method. Liver samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 39 publications
(74 reference statements)
2
32
2
Order By: Relevance
“…In contrast, unsaturated fat intake was associated with a decrease in lipolysis, preventing the accumulation of fat in the liver . The SFA diet has also been linked to impaired glutathione metabolism and an increase in oxidative stress, which leads to the progression of NAFLD . However, at present, it is not clear whether different sources of SFA (for example, dairy vs meat) can have different effects on liver fat content.…”
Section: Influence Of Dietary Macronutrients On Non‐alcoholic Fatty Lmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, unsaturated fat intake was associated with a decrease in lipolysis, preventing the accumulation of fat in the liver . The SFA diet has also been linked to impaired glutathione metabolism and an increase in oxidative stress, which leads to the progression of NAFLD . However, at present, it is not clear whether different sources of SFA (for example, dairy vs meat) can have different effects on liver fat content.…”
Section: Influence Of Dietary Macronutrients On Non‐alcoholic Fatty Lmentioning
confidence: 99%
“…4 The SFA diet has also been linked to impaired glutathione metabolism and an increase in oxidative stress, which leads to the progression of NAFLD. 5 However, at present, it is not clear whether different sources of SFA (for example, dairy vs meat) can have different effects on liver fat content. On the other hand, it is also important to consider that the effects of saturated fats seem to depend on a patient's genetic background.…”
Section: The Role Of Fatsmentioning
confidence: 99%
“…In order to study the process of adipogenesis of human SGBS cells we decided to use the novel targeted Lipidyzer™ technology. Although originally developed and validated for the fast and automated analysis of human plasma samples [ 20 ], recently published studies also showed good performance of the Lipidyzer™ assay with other matrices than plasma [ 21 , 22 , 23 , 24 , 25 ]. With the aim to obtain a meaningful “fit for purpose method”, we investigated the analytical performance regarding linearity and repeatability for the SGBS cells.…”
Section: Resultsmentioning
confidence: 99%
“…The hepatic lipid composition of DAG species may, in turn, strongly affect insulin sensitivity. However, the alteration in hepatic DAG levels has not confirmed by Franko et al [54], which supported the idea that PNPLA3 variation is tightly associated with fatty liver, but not with IR, whereby dissociating these two hallmarks of MAFLD. Indeed, IR-related MAFLD is characterized by high levels of metabolically harmful saturated and mono-unsaturated TG, ceramides and free fatty acids (FFAs), whereas PNPLA3-related MAFLD by hepatic PUFA-containing TG.…”
Section: Pnpla3: the Best Predictor Of Inheritable Mafldmentioning
confidence: 89%